Material Development of English Correspondence Using Task-Based Approach (TBA) for UNNES Students - Faridi, Abdurrachman; Rozi, Fahrur; Nurmasitah , Siti (KnE Social Sciences, 2019)
This study aimed to depict Unnes students’ ability in writing formal letters using English; design and develop correspondence material for English subject in Unnes; and evaluate the effectiveness of correspondence learning by applying Task Based Approach (TBA). This study has been done within a year in Universitas Negeri Semarang by using Research and Development approach. The results indicated that most of the students did not understand formal letter writing using English proven by their lack of knowledge about types of formal letter, letter style, and concept of letter sections. The main problems encountered by the students were garmmar, spelling, and punctuation. Thus, Task Based Approach (TBA) is an effective learning model to teach English correspondence. Correspondence material designing is an urgent need in regards to the advantages obtained by the students that is to develop their skills and ability in writing formal letter in English. Keywords: Letter, effectiveness, Task Based Approach (TBA)